Shoulder injuries in soccer goalkeepers: review and development of a FIFA 11+ shoulder injury prevention program - Ejnisman, B.; Barbosa, G.; Andreoli, C. V.; de Castro Pochini, A.; Lobo, T.; Zogaib, R.; Cohen, M.; Bizzini, M.; Dvorak, J. (Open Access Journal of Sports Medicine, 2016)
In the last years, shoulder injuries have represented an increasing health problem in soccer players. The goalkeepers are more exposed to shoulder disorders than other field players. Injury prevention exercises for upper limbs were cited in few studies involving throwing athletes, but we know that goalkeepers need a specific program. The purpose of this study is to describe the development of an adapted Fédération Internationale de Football Association (FIFA) 11+ program, namely the FIFA 11+ shoulder, which targets the prevention of shoulder injuries in soccer goalkeepers. The FIFA 11+ shoulder program is structured into three parts: general warming-up exercises, exercises to improve strength and balance of the shoulder, elbow, wrist, and finger muscles, and advanced exercises for core stability and muscle control. The exercises were selected based on recommendations from studies demonstrating high electromyographic activity.